Factors Related to Suicide Attempts: The Roles of Childhood Abuse and Spirituality - Tae, Hyejin; Chae, Jeong-Ho (Frontiers in Psychiatry, 2021)
Objectives: The purpose of this article was to identify independent factors associated with suicide attempts in patients with depression and/or anxiety. Background and aims: This study was conducted in order to examine whether risk and protective psychological factors influence the risk of suicide attempts among outpatients with anxiety and/or depressive disorders. In this regard, explanatory models have been reported to detect high-risk groups for suicide attempt. We also examined whether identified factors serve as mediators on suicide attempts. Materials and methods: Patients from 18 to 65 years old from an outpatient clinic at Seoul St. Mary’s Hospital were invited to join clinical studies. From September 2010 to November 2017, a total of 737 participants were included in the final sample. The Beck Depression Inventory (BDI), State-Trait Anxiety Inventory (STAI), Childhood Trauma Questionnaire (CTQ), Functional Assessment of Chronic Illness Therapy-Spiritual Well-being Scale (FACIT-Sp-12), and Functional Social Support Questionnaire (FSSQ) were used to assess psychiatric symptoms. An independent samples t-test, a chi-square test, hierarchical multiple regression analyses, and the Baron and Kenny’s procedures were performed in order to analyze data. Results: Young age, childhood history of emotional and sexual abuse, depression, and a low level of spirituality were significant independent factors for increased suicide attempts. Depression was reported to mediate the relationship between childhood emotional and sexual abuse, spirituality, and suicide attempts. Conclusions: Identifying the factors that significantly affect suicidality may be important for establishing effective plans of suicide prevention. Strategic assessments and interventions aimed at decreasing depression and supporting spirituality may be valuable for suicide prevention.